2019
DOI: 10.17109/azh.65.suppl.33.2019
|View full text |Cite
|
Sign up to set email alerts
|

Restoration trajectory of carabid functional traits in a formerly afforested blanket bog

Abstract: The restoration of peatland function and services on damaged peatland sites is seen as an increasingly important goal for ecological, environmental and societal reasons. Restoration monitoring often places fauna as secondary in importance to water table depth and vegetation, and when carried out, it often focuses on taxonomic indices. The use of functional traits, however, can be a complementary approach that clarifies mechanistic links between biodiversity and ecosystem functioning. This study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…(2006) found that large flightless Carabus species favoured an extensive grazing regime over an intensive one. However, other research has failed to find species that are indicators of different management treatments within habitat mosaics (Pravia et al ., 2019). This is in line with our own findings in which we did not identify species or assemblages that were particularly associated with different intensities of grazing at our site, including no evidence that some species preferred the less intensively grazed plots that might equate to a more extensive grazing regime.…”
Section: Discussionmentioning
confidence: 99%
“…(2006) found that large flightless Carabus species favoured an extensive grazing regime over an intensive one. However, other research has failed to find species that are indicators of different management treatments within habitat mosaics (Pravia et al ., 2019). This is in line with our own findings in which we did not identify species or assemblages that were particularly associated with different intensities of grazing at our site, including no evidence that some species preferred the less intensively grazed plots that might equate to a more extensive grazing regime.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat restoration can positively influence insect community reassembly [ 6 , 7 , 8 ], and a focus specifically on insect communities can promote essential ecosystem services such as pollination, pest control, carrion and waste removal, and food resources for other organisms [ 9 , 10 , 11 , 12 ]. One key invertebrate group that provides ecosystem services [ 10 ], is heavily impacted by human-imposed stressors [ 13 ], and responds positively to habitat restoration [ 14 , 15 ] is the ground beetles (Coleoptera: Carabidae). Ground beetles fill several crucial niches within ecosystems as predators, seed dispersers, and prey for other organisms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%